2021
DOI: 10.3389/fpsyg.2021.782833
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health of Caregivers and Their Patients With Dementia During the COVID-19 Pandemic: A Systematic Review

Abstract: Background: Coronavirus Disease 2019 (COVID-19) is a worldwide public health concern. It continues to spread rapidly throughout the world causing multiple physical and psychological consequences in the population. Especially, people affected by severe psychiatric or neurological diseases are highly susceptible to serious health complications not only due to the direct effect of the infection but also to the indirect effect of COVID-19 following social distancing during lockdowns and its general social conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 46 publications
3
14
0
4
Order By: Relevance
“…Existing reports indicate that the COVID-19 pandemic has posed significant social, psychological, emotional, and physical challenges to family members and friends who provide care for people with dementia. [604][605][606][607][608][609] Fatigue and burnout among dementia caregivers and their lack of access to services and supports for themselves and for the people for whom they provide care are common themes in research on the wide-ranging effects of the COVID-19 pandemic. For these reasons the pandemic has created a crisis for dementia caregivers.…”
Section: Covid-19 and Dementia Caregivingmentioning
confidence: 99%
“…Existing reports indicate that the COVID-19 pandemic has posed significant social, psychological, emotional, and physical challenges to family members and friends who provide care for people with dementia. [604][605][606][607][608][609] Fatigue and burnout among dementia caregivers and their lack of access to services and supports for themselves and for the people for whom they provide care are common themes in research on the wide-ranging effects of the COVID-19 pandemic. For these reasons the pandemic has created a crisis for dementia caregivers.…”
Section: Covid-19 and Dementia Caregivingmentioning
confidence: 99%
“…Our findings suggest the need to implement specific programs for caregivers to learn “coping” skills, socialization, support groups, online interventions to reduce stress, anxiety and depression [ 37 , 44 , 45 , 46 ]. A rigorous examination is also required to detect caregivers with symptoms of anxiety, depression, or burnout, particularly in females and caregivers co-living with the patient where apparently the risk is higher [ 27 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“… 27 The median survival years of patients with PIs and advanced dementia concomitantly was significantly shorter. 14 Carbone et al 28 reported a considerable increase in the psychological and physical burden of caregivers of patients with cognitive impairment or dementia during COVID‐19 confinement and an overall worsening of the clinical condition of patients with dementia. The multifaceted health needs of patients with dementia were largely neglected during the emergency phases of the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%